2017
DOI: 10.5455/medarh.2017.71.16-19
|View full text |Cite
|
Sign up to set email alerts
|

Training as an Effective Tool to Increase the Knowledge About Hand Hygiene Actions. An Evaluation Study of Training Effectiveness in Kosovo

Abstract: Introduction:Hand hygiene (HH) compliance with World Health Organization (WHO) guidelines is essential to prevent bacterial transmission and infections acquired from hospital settings.Aim:The aim of this study was to evaluate the impact of training tool of World Health Organization’s (WHOs) Hand Hygiene multi modal campaign at all public hospitals and at the University Clinical Center in Kosovo (UCCK).Method:During February 2016, 691 questionnaires were distributed to health care workers. The data collection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…An increase by 10% of nurses with university degree reduced the mortality risk by 5% and 9 % ( 20 , 21 ). In this context, nursing education should serve as a platform for continuous learning throughout life ( 22 , 23 ). This paper found that with the growth of work experience, the nurses’knowledge increases, the attitudes and practices improve by transforming into models for younger employees (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…An increase by 10% of nurses with university degree reduced the mortality risk by 5% and 9 % ( 20 , 21 ). In this context, nursing education should serve as a platform for continuous learning throughout life ( 22 , 23 ). This paper found that with the growth of work experience, the nurses’knowledge increases, the attitudes and practices improve by transforming into models for younger employees (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Although the procedure is easy to follow and there are numerous scientific publications recommending it, the extent to which nurses follow these recommendations for hand hygiene procedures still remains below the desired level [ 3 , 14 , 15 , 16 ]. The reasons which hinder proper compliance with hand hygiene procedures, and thus, prevent obtaining a high level of proper results include: overburden with care-related duties, limited time to perform this procedure, hand irritation, allergy to chemicals, insufficient supply of disinfectants as well as understaffing and lack of sufficient knowledge, experience and education in this field among medical staff [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the measures taken by the organizations, the education (initial or continuous training) of their healthcare worker has been of the main pillars to prevent biological exposure and accidents [ 11 ]. Despite the modifications and inclusion of initial and continuous training carried out during more than two decades, the level of knowledge and compliance with universal precautions procedures continues to be limited [ 12 , 13 ]. This difficulty in achieving optimum levels of knowledge seems to be linked to the reduced safety culture [ 14 ].…”
Section: Introductionmentioning
confidence: 99%